LEGAL PROBLEM DURING COVID-19 PANDEMIC IN INDONESIA: IS IT NECESSARY TO DECLARE IT TO BE AN EMERGENCY? - Wicipto Setiadi, Melta Setya Rahayu Pujianti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research discusses the constitutional basis of emergency in Indonesia, evaluation of emergency law, and urgency of emergency lawformulation. Article 12 of the 1945 Constitution of the Republic of Indonesia is the only constitutional basis of emergency. This research employed a normative legal research method and statute and conceptual approaches. The research result shows that the onlyemergency law referring to Article 12 of the 1945 Constitution of the Republic of Indonesia is Government Regulation in Lieu of Law No. 23 of 1959 concerning State of Emergency. Article 12 of the 1945 Constitution of the Republic of Indonesia is not referred to in emergency law formulation since the article is the concept of constitutional dictatorship. There is a trauma of the past since the application of constitutional dictatorshiptends to be used by Presidentto perpetuate their power. However, after the 1945 Constitution of the Republic of Indonesia regime, the checks and balancesand power division principles have been applied, thus although Presidentserves as the holder ofemergency power, but President does not have absolute power. Formulation of emergency law in Indonesiamay be returned to its constitutional path, which is to refer to Article 12 of the 1945 Constitution of the Republic of Indonesiaas the constitutional basis.